π-π interactions drive the homotypic phase separation of the prion-like diatom pyrenoid scaffold PYCO1 - Poh, Cheng Wei (2025)
CO2 fixation in most unicellular algae relies on the pyrenoid, a biomolecular condensate, which sequesters the cell's carboxylase Rubisco. In the marine diatom Phaeodactylum tricornutum, the pyrenoid tandem repeat protein Pyrenoid Component 1 (PYCO1) multivalently binds Rubisco to form a heterotypic Rubisco condensate. PYCO1 contains prion-like domains and can phase-separate homotypically in a salt-dependent manner. Here we dissect PYCO1 homotypic liquid-liquid phase separation (LLPS) by evaluating protein fragments and the effect of site-directed mutagenesis. Two of PYCO1's six repeats are required for homotypic LLPS. Mutagenesis of a minimal phase-separating fragment reveals tremendous sensitivity to the substitution of aromatic residues. Removing positively charged lysines and arginines instead enhances the propensity of the fragment to condense. We conclude that PYCO1 homotypic LLPS is mostly driven by π-π interactions mediated by tyrosine and tryptophan stickers. In contrast π-cation interactions involving arginine or lysine are not significant drivers of LLPS in this system.